Gaya Storynomics Tempat Wisata Berbasis Kerajaan dan Sejarah sebagai Bahan Ajar BIPA Korea Level Menengah Tinggi dan Lanjut - Kusmiatun, Ari; Triono, Eko (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
BIPA learning integrated with cultural tourism is increasingly implemented; however, available teaching materials remain largely descriptive and have not sufficiently fostered intercultural competence. Narrative approaches such as storynomics offer potential to bridge cross-cultural understanding, particularly in the cultural relationship between Indonesia and South Korea. This study aims to describe BIPA students’ perceptions of kingdom-based tourism as teaching material, identify key dimensions of student responses to the implementation of storynomics, and map Indonesian–South Korean storynomics patterns adaptable for BIPA instruction. A qualitative approach was employed using questionnaires, observations, and interviews seven South Korean students. Data were analyzed through descriptive statistics and thematic exploration. The findings reveal three main dimensions thatinfluence student perceptions: engagement with royal narratives that generate meaningful learning, preference for intercultural approaches over monocultural ones, and the need for critical reflection on cultural symbols. Comparative analysis indicates contrasting orientations: South Korea emphasizes digitization and standardization, whereas Indonesia prioritizes authenticity and philosophical depth. These findings suggest that cross-cultural narratives provide a foundation for developing BIPA teaching materials. This study recommends developing storynomics-based material prototypes integrating elements of Indonesian and Korean royal culture to support intercultural learning. These implications provide practical direction for the development of BIPA teaching materials.